PSVII-3 Evaluation of dietary OmniGen AF supplementation and PG600 injection on reproductive characteristics of gilts. (8th October 2021) - Chen, Jun; Lee, Jung Wook; Monegue, Jim J; Niblett, Richard; Williams, Kim; Estienne, Mark J; Chapman, Jim; Humphrey, Brooke; Lindemann, Merlin D
Abstract: A cooperative study evaluated effects of supplemental dietary OmniGen AF (OG; Phibro Animal Health Corporation) on reproductive characteristics of gilts. Crossbred gilts (n = 56; initial body weight = 152.3 ± 9.7 kg) were assigned to treatments in a 2 x 2 factorial design [diet (OG or control) and PG600 (Merck Animal Health, El Dora, KS) injection (Yes or No)]. Dietary treatments were: 1) corn-SBM basal diet (control) that met NRC (2012) requirement estimates, or 2) control plus 0.75% OG and were fed 35 to 40 d prior to breeding. A common diet formulation was used by both stations. Gilts were estrous-synchronized by 14-d feeding of Matrix (Merck Animal Health). PG600 injections occurred 24 hours after Matrix withdrawal. Gilts were weighed at breeding and preslaughter (at d 39 to 48 postbreeding) and were euthanized to evaluate reproductive characteristics. There were no OG x PG600 interactions on any response measures (P > 0.15). Mean responses did not differ (P > 0.20) when gilts were fed control or OG diets, respectively, for total uterus weight (6, 065 vs. 5, 883 g), uterine horn length (129.2 vs. 123.9 cm), ovary weight (9.66 vs. 9.94 g), total corpora lutea (CL) number (25.0 vs. 25.3), individual CL weight (0.41 vs. 0.43 g), total follicular fluid weight (3.17 vs. 3.03 g), individual placenta weight (86.3 vs. 86.4 g), total fetuses (14.2 vs. 13.0), and fetus crown-rump length (7.97 vs. 7.66 cm). Supplementation with OG reduced (P = 0.04) individual placenta fluid volume of gilts (150.6 vs. 115.4 mL). PG600 injection increased (P < 0.001) ovary weight (9.03 vs. 10.57 g), total CL (18.09 vs 32.27) and reduced CL weight (0.46 vs. 0.38 g). The results demonstrated classic PG600 responses on reproductive characteristics but no effects of 0.75% OG supplementation nor an interaction between the two factors.